PENGARUH PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR PESERTA DIDIK PEMBELAJARAN JEPIN MASSAL KELAS VIII - Sherly Widya Anggraini; Winda Istiandini; Asfar Munir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
ABSTRACT The purpose of this thesis is to get information about the effect of cooperative learning model type “snowball throwing” to the students’ learning result in teaching traditional dance in garde eighth (VIII) SMPN12 Pontianak. This thesis used experiment method by using true experimental design. Based on the statistical calculation, the students score average in the experimental class was 80,97 with the lowest score was 64 and the highest score was 96. Meanwhile, the students score average in the control class was 75,71 with the lowest score was 60 and the highest was 88. The result of data analysis by using the Ttest showed that calculated T( Thitung) was 2,39 with the dk = 34 + 31 – 2 = 63 and significancy value (α = 5%). So that the researcher had the value of Ttabel was 1,999. The data showed that Thitung was higher than Ttable or (2,39 > 1,999) that meant the data was significant. It showed that there was an effect of using cooperative learning model type “’snowball throwing to the students” learning result of traditional dance lesson material in grade eight (VIII) of SMPN 12 Pontianak Keywords: effect, learning model snowball throwing, learning result, Traditional dance.